OS3.3 Radiological characteristics and natural history of adult IDH wild type astrocytomas with TERT promoter mutations. (19th September 2018) - Izquierdo, C; Barritault, M; Poncet, D; Cartalat, S; Joubert, B; Bruna, J; Jouanneau, E; Guyotat, J; Vasiljevic, A; Fenouil, T; Berthezène, Y; Honnorat, J; et al.
Abstract: Background: Adult IDH -wildtype astrocytomas with TERT promoter mutations ( TERTp ) are associated with a poor prognosis. The aim of the present study was to analyze their radiological presentation and natural history. Material and Methods: We retrospectively reviewed the characteristics of 40 IDH -wildtype TERTp -mutant astrocytomas (grade II n=19, grade III n=21) and compared them to those of 114 IDH -mutant lower grade gliomas (LGG), of 92 IDH -wildtype TERTp -mutant glioblastomas and of 15 IDH -wildtype TERTp -wildtype astrocytomas. Results: Most cases of IDH -wildtype TERTp -mutant astrocytomas occurred in patients aged >50 years (88%) and presented as infiltrative lesions without contrast enhancement (73%) that were localized in the temporal and/or insular lobes (37.5%) or corresponded to a gliomatosis cerebri (43%). Thalamic involvement (33%) and extension to the brainstem (27%) were frequently observed, as was gyriform infiltration (33%). This radiological presentation was different from that of IDH -mutant LGG, IDH -wildtype TERTp -mutant glioblastomas, and IDH -wildtype TERTp -wildtype astrocytomas. Tumor evolution before treatment initiation was assessable in 17 cases. Ten cases demonstrated a rapid growth characterized by the apparition of a ring-like contrast enhancement and/or a median velocity of diametric expansion (VDE) ≥ 8 mm/year but 7 cases displayed a slow growth (VDE < 8 mm/year) that could last several years before anaplastic transformation. Median overall survival of IDH -wildtype TERTp -mutant astrocytomas was 27 months. Conclusion: IDH -wildtype TERTp -mutant astrocytomas typically present as non-enhancing temporo-insular infiltrative lesions or as gliomatosis cerebri in patients aged >50 years. In the absence of treatment, although rapid tumor growth is frequent, an initial falsely reassuring, slow growth can be observed.